2015
DOI: 10.1055/s-0035-1569257
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Wide-Detector CT Kinematic Evaluation: From Motion to Image

Abstract: Kinematic computed tomography (CT) allows identification of fine positional anomalies of bones during motion and under stress and has a potential role in the evaluation of dynamic joint diseases. The increasing width of CT detector systems has made kinematic CT clinically available. Information on acquisition protocol, patient preparation, and the influence of motion on image quality is scarce in the literature despite the obvious importance for the clinical application of this technique. In this article we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, Euclidean distance maps of the ground truth manual segmentations and the surface of the corresponding segmentation obtained from the atlas-based method, were used to compute the Hausdorff distance [34]. Equation (7) shows the definition of the Hausdorff distance.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Euclidean distance maps of the ground truth manual segmentations and the surface of the corresponding segmentation obtained from the atlas-based method, were used to compute the Hausdorff distance [34]. Equation (7) shows the definition of the Hausdorff distance.…”
Section: Validationmentioning
confidence: 99%
“…Dynamic computer tomography (4D-CT) enables acquisition of a series of high temporal-resolution 3D CT datasets of moving structures. Various phantom studies [6][7][8][9] demonstrated the validity and feasibility of dynamic CT for evaluating MSK diseases. Several patient studies have been conducted investigating different joint disorders of the wrist, knee, hip, shoulder and foot [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in-vivo analysis of articular motion can be performed by several techniques [11]: ultrasonography [12], fluoroscopy [13], computed tomography (CT) [14], and Magnetic Resonance Imaging (MRI) [6]. Ultrasonography, however, is limited to the evaluation of soft tissues around the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Four-dimensional computed tomography (4DCT) is an increasingly popular imaging modality and in the last decade, its applications for musculoskeletal (MSK) investigations have become more apparent 13 . Within this modality, one of the main applications reported so far is the estimation of integrity of (intra-)articular ligaments and the analysis of complex motion in several joints with strong rotatory components 4 .…”
Section: Introductionmentioning
confidence: 99%